Evaluation of the accuracy of a multi-infection screening test based on a multiplex immunoassay targeting imported diseases common in migrant populations - Ruth Aguilar; Angeline Cruz; Alfons Jiménez; Alex Almuedo; Carme Roca Saumell; Marina Gigante Lopez; Oriol Gasch; Gemma Falcó; Ana Jiménez-Lozano; Angela Martínez-Perez; Consol Sanchez-Collado; Andrea Tedesco; et al. (Travel Medicine and Infectious Disease, 2024)
Background: We aimed to evaluate the performance of a novel multiplex serological assay, able to simultaneously detect IgG of six infections, as a screening tool for imported diseases in migrants. Methods: Six panels of 40 (n = 240) anonymized serum samples with confirmed infections were used as positive controls to assess the multiplex assay's sensitivity. One panel of 40 sera from non-infected subjects was used to estimate the seropositivity cutoffs, and 32 non-infected sera were used as negative controls to estimate each serology's sensitivity and specificity. The multi-infection screening test was validated in a prospective cohort of 48 migrants from endemic areas.The sensitivity of the Luminex assay was calculated as the proportion of positive results over all positive samples identified by reference tests. The specificity was calculated using 32 negative samples. Uncertainty was quantified with 95 % confidence intervals using receiver operating characteristic analyses. Results: The sensitivity/specificity were 100 %/100 % for HIV (gp41 antigen), 97.5 %/100 % for Hepatitis B virus (HBV-core antigen), 100 %/100 % for Hepatitis C virus (HCV-core antigen), 92.5 %/90.6 % for strongyloidiasis [31-kDa recombinant antigen (NIE)], 97.5 %/100 % for schistosomiasis (combined serpin Schistosoma mansoni and S.haematobium antigens) and 95 %/90.6 % for Chagas disease [combined Trypanosoma cruzi kinetoplastid membrane protein-11 (KMP11) and paraflagellar rod proteins 2 (PFR2) antigens].In the migrant cohort, antibody response to the combination of the T.cruzi antigens correctly identified 100 % individuals, whereas HBV-core antigen correctly identified 91.7 % and Strongyloides-NIE antigen 86.4 %. Conclusions: We developed a new, robust and accurate 8-plex Luminex assay that could facilitate the implementation of screening programmes targeting migrant populations.